Maternal factors epigenetically alter Hippo signaling pathway leading to impaired cell fate specification of neural stem cells during brain development (Invited Talk) - Dheen, Shaikali Thameem (2020)
International conference on Reproduction, Endocrinology and Development (ICRED)